Hamstring Autograft for Foot and Ankle Applications. Issue 3 (11th September 2017) - Cody, Elizabeth; Karnovsky, Sydney; DeSandis, Bridget; Tychanski, Andrea; Deland, Jonathan; Drakos, Mark
Category: Ankle, Sports Introduction/Purpose: Hamstring tendon autografts (gracilis and/or semitendinosus) may be used as an alternative to allograft or local tendon grafts in foot and ankle surgery, primarily for tendon or ligament repairs in which direct repair has failed or is not possible. Advantages of hamstring autografts include avoiding the expense and lower healing potential of allografts, as well as the morbidity associated with local tendon grafts. While hamstring harvest has been abundantly studied in the setting of concomitant knee surgeries, few authors have investigated its effects when used specifically for foot and ankle applications. We studied a cohort of patients who underwent hamstring harvest for foot and ankle applications, hypothesizing that morbidity to the knee would be limited and foot and ankle outcome scores would be good. Methods: All patients who underwent hamstring autograft for foot or ankle applications by a fellowship-trained sports surgeon since 2011 were screened for inclusion. Patients were eligible if they were over the age of 18, had no history of knee pathology, and were at least one year from surgery. 23 patients were enrolled an average of 23 months post-operatively (range, 12-59 months). The average age was 51 ± 18 (range, 18-77) and 50% were women. Isokinetic testing was performed using a Biodex dynamometer, with the administering physical therapist blinded to side of surgery. Peak flexion and extension torque as well as flexion and extension torque at 30, 70, and 90 degrees of flexion were collected at two different testing speeds, 180 and 300 degrees/second. Pre- and post-operative questionnaire scores—the Foot and Ankle Outcome Score (FAOS) and Short Form (SF)- 12—were retrospectively reviewed. T-tests were used for all comparisons. Results: Of the 23 patients enrolled, gracilis was harvested in 14, semitendinosus in six, and both tendons in three to reconstruct the lateral ankle ligaments (eight patients), tibialis anterior (six), Achilles (five), and peroneus brevis (four). At follow-up, 19 patients (83%) reported no pain at the harvest site; the remaining four patients reported mild to moderate symptoms. There were no significant differences between relative flexion strength at different degrees of flexion or between relative flexion and extension strength, with strength considered as a percentage of that of the non-operated leg (Table). All five FAOS subscales and the SF-12 physical component subscale improved significantly (p=0.01 for all). No patients were dissatisfied and all would recommend the surgery to someone else. Conclusion: When used for foot and ankle surgery, hamstring autografts result in good functional outcomes and high patient satisfaction, with few patients experiencing symptoms from the harvest site at follow-up. Although our study was limited by its small number of patients and lack of preoperative isokinetic testing for comparison, effects on knee flexion strength do not appear to be clinically significant. Further work with larger numbers of patients will be required to identify small effects on knee flexion strength and to delineate differences between harvesting gracilis and semitendinosus.